Programa de intervención para la prevención de incendios forestales en los estudiantes del tercer año de bachillerato en agropecuaria del colegio Técnico Gonzanamá, desde el enfoque del autodesarrollo comunitario. - Ludeña Sánchez, Jaime Oswaldo (2013)
The present work of a qualitative kind collects so synthesized the results of the research: "Program of Intervention for the Prevention of Forest Fires in the students in the third year of School in Agricultural Technical Gonzanamá College, since the approach of Community self", developed within the framework of the Master's Degree in Community Development offered by the National University of Loja. Research that was improve since the alternative of social empowerment that offers us the community self, the same that we allowed through informal working sessions (initial exchange with the subject need of professional action - I Stage) with the students determine the degree of training, commitment and social sense and impact that produces in them the problem of forest fires; activity implemented through reflective processes. Well, thanks to the implementation of interviews with authorities of the high school, specialists in the topic and people committed to nature and its preservation; as to the comment made by the researcher, will complement what the opportunities are and/or existing forms in the community, to develop the interest in the conservation of nature (formulation of the pre diagnosis - II Stage), today for today so exploited and almost invisibility or considered an inexhaustible source of exploitation and enrichment naturalized. With this background is obtained the arguments to that of the working group will emerge on the empirical data and theoretical references - contextualization - offered by the facilitator of the process, the areas that need to be object of intervention for the prevention of forest fires (process in if diagnostic and search for solutions - III Stage). It should be noted that of the five stages, which are part of the Community self, in this document is work up to the third stage, reaching to structure a proposal that will allow the students the questioning of everyday life for the strengthening of a critical consciousness that enable the analyze what are the causes that must be corrected in the implementation of their own community project that involves all of the affected community in the search for possible solutions.